Ответы и объяснения

2014-03-26T06:28:42+00:00
1)   \left \{ {{ \sqrt{8- \frac{x}{4} } =6} \atop {8- \frac{x}{4} >0} \right.

8- \frac{x}{4} =36

 \frac{x}{4} =-36-8

x=-24

2)   \sqrt[3]{35- x^{2} } =2

  35- x^2 =2^3=8

  x^2 =35-8

  x^2=27

  x_1 =3\sqrt{3}

  x_2 =-3\sqrt{3}

3)   \left \{ {{ \sqrt{x^2-5}= \sqrt{4x}  } \atop {x ^2-5>0(  4x>0)}}

{x^2-5}= {4x}

x^2-4x-5= 0

{x_1=5

{x_2=-1 не подх 

4)   \left \{ {{x^2-5x-104=0} \atop {x^2+5x-24 \neq 0 (x \neq -8)(x \neq 3)}} \right.

x^2-5x-104=0

x^2-5x-104=0

D=25+416=441

 \sqrt{D} =21

x_1=13

x_2=-8  (не подх)

5) (x-12)(x+4)(x-3)(x+1)=0

x_1=12

x_2=-4

x_3=3

x_4=-1

6)  5^{x+3}-11^2*5^x=10^2

5^{x}*5^3-11^2*5^x=2^25^2

5^{x}(5^3-11^2)=4*5^2

5^{x}(125-121)=4*5^2

5^{x}*4=4*5^2

x=2

7) 2^{x-1}+2^x=2^{x+1}-4

 2^{x}(2^{-1}+1)=2^{x}*2-2^2

 2^{x}*(-\frac{1}{2})=-2^2

2^{x}*2^{-1}=2^2

2^{x-1}=2^2

x=3

8)  x^8-13x^4-48=0

 x^4=t

 t^2-13t-48=0

D=169+192=361

 \sqrt{D} =19

 t_1=16

 t_2=-3 не подх

x^4=16

x_1=2

x_2=-2